The Influence Of Green Human Resource Management On Employees' Green Behavior - Elvira Azzahra; Dina Mellita (TALENTA Publisher, Universitas Sumatera Utara, 2024)
This research aims to determine the effect of environmentally friendly recruitment selection, environmentally friendly training, environmentally friendly performance management, environmentally friendly payments & rewards, and environmentally friendly involvement on employee green behavior. The method used is quantitative, the research object is employees of PT. Bukit Asam Tbk Tanjung Enim City. Respondents in this research were employees of PT. Bukit Asam Tbk Tanjung Enim as many as 95 people collected data using a questionnaire. This research sample was taken using a simple random sampling technique, namely taking samples from the population randomly without distinguishing between education, position or status. The data analysis technique was carried out using SPSS version 29. Based on the results of multiple linear regression analysis research, variables were obtained that influence employee green behavior, namely green training, green pay & rewards and green involvement at PT. Bukit Asam Tbk. Meanwhile, variables that do not influence employee green behavior are environmentally friendly recruitment selection and environmentally friendly performance management at PT. Bukit Asam Tbk.